Music management, marketing and PR - Anderton, Chris; Hannam, James; Hopkins, Johnny (SAGE Publications, 2022)
"This book is your guide to the study and practice of music management and the fast-moving music business of the 21st century. Covering a range of careers, organisations, and practices, this expert introduction will help aspiring artists, managers, and executives to understand and succeed in this exciting sector. Featuring exclusive interviews with industry experts and discussions of well-known artists, it covers key areas such as artist development, the live music sector, fan engagement, and copyright. Other topics include : Managing contracts and assembling teams. Using data audits of platforms to adapt campaigns. Shaping opinions about music, musicians, events.How the music industry can be more diverse, inclusive, and equitable for the benefit of all.Working with venues, promoters, booking agents, and tour managers. Branding, sponsorship, and endorsement. Funding, crowdsourcing and royalty collection. Ongoing digital developments such as streaming income and algorithmic recommendation. Balancing the creative and the commercial, it is essential reading for students of music management, music business, and music promotion – and anybody looking to build their career in the music industries."--